Risk factors for complicated parapneumonic effusion and empyema on presentation to hospital with community-acquired pneumonia. Issue 7 (8th January 2009) - Chalmers, J D; Singanayagam, A; Murray, M P; Scally, C; Fawzi, A; Hill, A T
Abstract : Background: The aim of this study was to identify key factors on admission predicting the development of complicated parapneumonic effusion or empyema in patients admitted with community-acquired pneumonia. Methods: A prospective observational study of patients admitted with community-acquired pneumonia in NHS Lothian, UK, was conducted. Multivariate regression analyses were used to evaluate factors that could predict the development of complicated parapneumonic effusion or empyema, including admission demographics, clinical features, laboratory tests and pneumonia-specific (Pneumonia Severity Index (PSI), CURB65 (New onset confusion, urea >7 mmol/l, Respiratory rate ≥30 breaths/min, Systolic blood pressure < 90 mm Hg and/or diastolic blood pressure ≤60 mm Hg and age ≥65 years) and CRB65 (New onset confusion, Respiratory rate ≥30 breaths/min, Systolic blood pressure <90 mm Hg and/or diastolic blood pressure ≤60 mm Hg and age ≥65 years)) and generic sepsis scoring systems (APACHE II (Acute Physiology and Chronic Health Evaluation II), SEWS (standardised early warning score) and systemic inflammatory response syndrome (SIRS)). Results: 1269 patients were included in the study and 92 patients (7.2%) developed complicated parapneumonic effusion or empyema. The pneumonia-specific and generic sepsis scoring systems had no value in predicting complicated parapneumonic effusion or empyema. Multivariate logistic regression identified albumin <30 g/l adjusted odds ratio (AOR) 4.55 (95% CI 2.45 to 8.45, p<0.0001), sodium <130 mmol/l AOR 2.70 (1.55 to 4.70, p = 0.0005), platelet count >400×10 9 /l AOR 4.09 (2.21 to 7.54, p<0.0001), C-reactive protein >100 mg/l AOR 15.7 (3.69 to 66.9, p<0.0001) and a history of alcohol abuse AOR 4.28 (1.87 to 9.82, p  =  0.0006) or intravenous drug use AOR 2.82 (1.09 to 7.30, p = 0.03) as independently associated with development of complicated parapneumonic effusion or empyema. A history of chronic obstructive pulmonary disease was associated with decreased risk, AOR 0.18 (0.06 to 0.53, p = 0.002). A 6-point scoring system using these combined variables had good discriminatory value: area under the receiver operator characteristic curve (AUC) 0.84 (95% CI 0.81 to 0.86, p<0.0001). Conclusion: This study has identified seven clinical factors predicting the development of complicated parapneumonic effusion or empyema. Independent validation is needed.